Mid and late Holocene multiproxy analysis of environmental changes linked to sea-level fluctuation and climate variability of the Río de la Plata estuary - Mourelle Civano, Dominique (2015)
In the present study, we carried out pollen, diatom and other palynomorph analyses from asedimentary sequence from the marshes of Arroyo Solís Grande, in the Río de la Plata northeastern coast (Uruguay), and compared the results with a regional model of surface pollen-vegetation relationship from the Atlantic coastal salt marshes (30°-37° S). Results indicated that salt marsh vegetation developed around the estuary between 8000 and 5100 cal yr BP, as the sea level rose and reached the Holocene sea-level highstand. Brackish marshes around the estuary between 5100 and 2900 cal yr BP reflect the late Holocene sea-level fall and associated increased input of freshwater. Brackish marshes and shallow salt pond environments between 2900 and 1000 cal yr BP are most probably linked to the Paraná delta formation and a further sea-level fall. Present-day marshes behind the sand bar characterize the last 1000 cal yr BP. The integration of our results with multiproxy records from the Río de la Plata southern coast (Argentina) and from the coastal plain of the southern Atlantic margin of South America (30°-37° S) revealed that marine influence during the maximum sea-level highstand resulted in the development of vegetation similar to that of the geographical region.However, after ca. 3000 cal yr BP, local differentiation related to different climate and geomorphology occurred at each area, thus resulting in the establishment of different modern plant communities at different times during the late Holocene.